Maternal education, health profession and cigarette smoking are decisive factors for self-medication in children by parents - Duborija-Kovacevic Natasa; Martinovic Milica; Belojevic Goran; Lausevic Dragan; Asanin Bogdan (Acta Pharmaceutica)
Self-medication of children by their parents (SMCP) is an important public health issue as the effects and potential risks may be unpredictable. The objective of this first national Montenegrin study was to assess the prevalence of and factors influencing SMCP among schoolchildren. Data were obtained from a national representative sample of 4496 schoolchildren aged 7–13 years (50.4 % boys). Parents/caregivers completed a questionnaire concerning their demographic characteristics, socio-economic and cultural status, as well as the self-medication (SM) of their children. The association between SMCP and parents’ socio-economic, demographic or cultural status was assessed by logistic regression analyses. The prevalence rate of SMCP was 24.6 %. Univariate logistic regression showed that maternal socio-demographic characteristics (educational level, employment status, health care profession and smoking habits) were relevant for SMCP. In a multiple logistic regression the independent effect /adjusted odds ratio (AOR) (95 % CI)/of maternal factors on SMCP remained for: education /2.23 (1.18–4.24)/, university-level vs. no education; profession /1.50 (1.07–3.00)/, health profession vs. non-health profession; and smoking habit /1.22 (1.04–1.42)/smokers vs. non-smokers. SMCP may be expected for every fourth child in Montenegro. Specific maternal factors that independently raise the probability of SMCP are higher education, health profession and smoking.